MAPPING THE QUALITY OF HR THROUGH THE APPROACH STRENGTH OF CHARACTER IN SUPPORTING THE POTENTIAL OF RELIGIOUS TOURISM VILLAGE IN GRESIK REGENCY, EAST JAVA (Universitas Dr. Soetomo, 2022)
The potential for large income from tourist villages and the government's strong push to develop tourism potential makes many villages want to develop tourism potential in their villages. Being a tourist village requires the readiness of human resources who are able to show excellent service to customers. This study aims to map the quality of human resources through a character strength approach in Giri Village to Support Religious Tourism Villages. The subject of this research is the community of Giri Village, Gresik Regency, East Java, with productive age (18-64 years) totaling 2,765 people, as a potential resource in supporting the Religious Tourism Village. The research sample was determined by a quota of 100 respondents. Data collection using VIA-IS and questionnaires. The data were analyzed quantitatively descriptively with the help of the SPSS program, to produce a map of the quality of human resources (HR) and the strength of community character in supporting the potential of the Religious Tourism Village in Gresik Regency, East Java. The results showed that human resource quality includes 1) fictional quality 23%, 2) intelligence quality 37%, 3) spiritual quality 40%. Strength of character consists of 1) integrity 20%, 2) gratitude 20%, 3) hope 20%, 4) fairness 20%, and 5) kindeness 20%, while support for Religious Villages are; 1) knowledge 23%, 2) involvement 27%, 3) ideas 23%, and 4) expectations 27%. This map and real conditions need to be analyzed further to provide recommendations and concrete steps towards future efforts to develop a Religious Tourism Village in Gresik Regency, East Java.